2004
DOI: 10.2165/00007256-200434090-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Effects of Chronic Hypoestrogenism in Amenorrhoeic Athletes

Abstract: In premenopausal women, the most severe menstrual dysfunction is amenorrhea and is associated with chronic hypoestrogenism. In postmenopausal women, the coincident hypoestrogenism observed is associated with a number of clinical sequelae related to cardiovascular health. Due to an observed cardioprotective effect of E2, persistently low E2 levels in amenorrheic (AM) athletes may confer deleterious effects on cardiovascular health.The incidence of amenorrhea among athletes is much greater than that observed amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 265 publications
0
19
1
1
Order By: Relevance
“…Additionally, in fertile age women hyperhomocysteinemia has been associated with amenorrhea, especially in female athletes (O'Donnell and De Souza 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in fertile age women hyperhomocysteinemia has been associated with amenorrhea, especially in female athletes (O'Donnell and De Souza 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the accepted cardiovascular benefits of exercise, studies of amenorrheic female athletes suggest an increased risk for early cardiovascular disease [31], whereas reports from observational studies have suggested that HRT decreases cardiovascular mortality in postmenopausal women [32]. However, the large randomized trial with placebo control, Heart and Estrogen/progestin Replacement Study (HERS), found that women with known cardiovascular disease had increased cardiovascular disease events during the first year of HRT use despite reported favourable benefit from randomized trials of HRT on total cholesterol (C), lipoproteins [increased high-density lipoproteins (HDLs) and decreased low-density lipoproteins (LDLs)], vasodilatation and reduced inflammation [32].…”
Section: Issues Of Hormone Replacement Therapy In Womenmentioning
confidence: 99%
“…Athletes with luteal deficiency may also be at risk for infertility due to poor follicular development or failure of implantation. Consequences of hypoestrogenism seen in amenorrheic athletes include impaired endotheliumdependent arterial vasodilation (78), which reduces the perfusion of working muscle, impaired skeletal muscle oxidative metabolism (75), elevated low-density lipoprotein cholesterol levels (59,154), and vaginal dryness (73).…”
Section: Health Consequencesmentioning
confidence: 99%